The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1242/jeb.158055
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic sensory threshold in harbour seals (Phoca vitulina) for artificial flatfish breathing currents

Abstract: Harbour seals have the ability to detect benthic fish such as flatfish using the water currents these fish emit through their gills (breathing currents). We investigated the sensory threshold in harbour seals for this specific hydrodynamic stimulus under conditions which are realistic for seals hunting in the wild. We used an experimental platform where an artificial breathing current was emitted through one of eight different nozzles. Two seals were trained to search for the active nozzle. Each experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Summarell et al (2015) found that smooth whiskers were stiffer than undulating whiskers. Since phocids, with undulating whiskers, tend to be better at hydrodynamic tasks (Gläser et al, 2011; Hanke et al, 2013; Krüger et al, 2018; Niesterok et al, 2017), the authors suggest that having some flexibility of the whiskers might be useful for hydrodynamic sensing in phocids, while stiffer whiskers might be better for touch sensing in otariids. While we suggest here that aquatic mammal whiskers are stiffer than those of terrestrial mammals, for otariids and phocids, a more complex three‐dimensional approach may be needed in order to fully compare whisker stiffness between these species, especially to better understand the functional significance of whisker stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarell et al (2015) found that smooth whiskers were stiffer than undulating whiskers. Since phocids, with undulating whiskers, tend to be better at hydrodynamic tasks (Gläser et al, 2011; Hanke et al, 2013; Krüger et al, 2018; Niesterok et al, 2017), the authors suggest that having some flexibility of the whiskers might be useful for hydrodynamic sensing in phocids, while stiffer whiskers might be better for touch sensing in otariids. While we suggest here that aquatic mammal whiskers are stiffer than those of terrestrial mammals, for otariids and phocids, a more complex three‐dimensional approach may be needed in order to fully compare whisker stiffness between these species, especially to better understand the functional significance of whisker stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in diameter between the major and minor axes can be quite variable; Grey seals (Halichoerus grypus) have more elliptical whiskers in cross-section, and Weddell seals (Leptonychotes weddellii) have more circular whiskers (Summarell et al, 2015). The most studied whisker adaptation in pinnipeds is the presence of undulations along the shaft, which are observable in most phocids (Ginter et al, 2010(Ginter et al, , 2012Gläser et al, 2011;Hanke et al, 2010;Krüger, Hanke, Miersch, & Dehnhardt, 2018;Niesterok, Dehnhardt, & Hanke, 2017;Summarell et al, 2015) (Figure 1a). These undulations are believed to reduce signal to noise ratios in flowing water (Hanke et al, 2010;Kottapalli, Asadnia, Miao, & Triantafyllou, 2015).…”
Section: Aquatic and Terrestrial Whiskersmentioning
confidence: 99%
“…Niesterok et al . experimented with intermittent jets from an underwater surface to imitate artificial flatfish breathing currents on sea lions and found that the seals could detect velocities in the range of 2–2.5 cm/sec 18 . This value is significantly higher than the value (0.25 mm/sec) obtained from dipole studies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Niesterok et al experimented on harbour seals by imitating artificial flatfish breathing currents. This was done by producing intermittent jets from an underwater surface and found that the seals could identify velocities in the range of 2-2.5 cm/sec 18 . This value is significantly higher than that of the value (0.25 mm/sec), attained from dipole experiments 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Harbour seals (Phoca vitulina) detect and analyse subsurface water motions not only of the sinusoidally oscillating dipole type (Dehnhardt et al 1998a), which bear some resemblance with the water movements generated by oscillating body parts, but also direct current water jets (Wieskotten et al 2011;Niesterok et al 2017a, b;Krüger et al 2018). Direct current water jets occur, for example, in the tail wake of fishes (Hanke and Bleckmann 2004;Niesterok and Hanke 2013), where they often form the central part of vortex rings, and in the breathing currents of fishes (Niesterok et al 2017b).…”
Section: Sensitivity To Horizontal Water Motionsmentioning
confidence: 99%